(untitled) (Research, Society and Development, 2022)
From the point of view of the dominant energy matrix based on fossil sources, technologies linked to fuel cells have gained much prominence in the scientific world. They can be seen as a future energy vector, especially when coupled with existing hydrogen saving techniques and renewable energy matrices. Thus, this study aims to promote the discussion about the use and application of fuel cells in substitution for the current energy system through the literature review technique. Fuel cells promote low emissions of greenhouse gases, nitrogen oxides, and sulfur (NOx and SOx); this allows a more significant reduction of environmental impacts. In addition, they can function on a small, medium, and large scale and can be reused for a wide range of applications. Among them is replacing cars powered by internal combustion engines with electric cars; these are more efficient in generating energy, with lower amounts of noise and environmental impacts.